Rahnella aquatilis Isolated from Aedes albopictus Impairs Mosquito Reproduction Capacity - Ling Gu; Lin Li; Jinyang Sun; Yongqiao Zhao; Kai Wan; Meichun Zhang; Julin Li; Meihua Zhang; Guoding Zhu; Jianxia Tang (Insects)
Aedes albopictus is one of the most important vectors of Dengue, which poses a serious threat to public health. The bacterial microbiota has an effect on the parameters of mosquitos, such as larval development and fecundity, and it has emerged as a promising field to be explored for novel environmentally friendly control strategies. Rahnella sp. are present in many insects, including Ae. Albopictus, and play a role in bacterial–insect interactions; however, the role of the bacteria in mosquito biology has not yet been characterized. In this study, we characterized the Rahnella isolate RAeA1 obtained from Ae. albopcitus, and its colonization stability in Ae. albopictus was investigated by generating GFP-tagged bacteria. The influences of the bacteria on larval development and mosquito reproductive capacity were evaluated by inoculating RAeA1 in axenic larvae and antibiotic-treated adult mosquitoes, respectively. The results indicated that RAeA1, which is widespread in the field population of Ae. albopictus, can be transmitted directly from the parental strain to the progeny and can rescue axenic larvae developing into adults with a prolonged development time to pupation. RAeA1 inoculation can impair egg production and ovary maturation, as well as reducing the synthesis of ecdysteroids and vitellogenin in Ae. albopictus females. Overall, our results provide a thorough study of bacterium function characterization that will facilitate the development of potential strategies in relation to the design of microbiomes for vector control.